Modern trigonometry : analysis and application - Barnett, Raymond A. (New Jersey, 2009)
Learning trigonometry concepts can be a difficult and frustrating process. The tenth edition of this successful book helps readers gain a strong understanding of these concepts by discovering how trigonometry is relevant in their lives through rich applications. It follows a right triangle-first approach and is graphing optional.
Keywords: Trigonometry